Using the Visual World Paradigm to Study Retrieval Interference in Spoken Language Comprehension - Sekerina, Irina A.; Campanelli, Luca; Van Dyke, Julie A. (Frontiers in Psychology, 2016)
The cue-based retrieval theory (Lewis, Vasishth, & Van Dyke, 2006) predicts that interference from similar distractors should create difficulty for argument integration, however this hypothesis has only been examined in the written modality. The current study uses the Visual World Paradigm (VWP) to assess its feasibility to study retrieval interference arising from distractors present in a visual display during spoken language comprehension. The study aims to extend findings from Van Dyke & McElree (2006), which utilized a dual-task paradigm with written sentences in which they manipulated the relationship between extra-sentential distractors and the semantic retrieval cues from a verb, to the spoken modality. Results indicate that retrieval interference effects do occur in the spoken modality, manifesting immediately upon encountering the verbal retrieval cue for inaccurate trials when the distractors are present in the visual field. We also observed indicators of repair processes in trials containing semantic distractors, which were ultimately answered correctly. We conclude that the VWP is a useful tool for investigating retrieval interference effects, including both the online effects of distractors and their after-effects, when repair is initiated. This work paves the way for further studies of retrieval interference in the spoken modality, which is especially significant for examining the phenomenon in pre-reading children, non-reading adults (e.g., people with aphasia), and spoken language bilinguals.